iProt – A Data Warehouse For Protein Database. - Jaya, M.I.; Zainol, Zurinahni; Ahamed Hassain Malim, N.H. (2007)
An integrated database is a vital approach to help biologist to analyze protein data from heterogeneous formats and resources. The iProt (Integrated Protein Data Warehouse) is a pool of protein dataset that provide a comprehensive protein sequence' 3D structure, enzymatic reaction, gene description, and taxonomical data from five different protein databases; Swiss-Prot, Protein Data Bank (PDB), ENZYME, NCBI Taxonomy and Gene Ontology (GO).